Integrated effects of cold acclimation: physiological mechanisms, psychological adaptations, and potential applications - Wang, Yongxing; Liu, Wei; Han, Dezhi; Qiao, Yaqun; Sun, Weijing; Wang, Conghui; Qin, Xiaoyong; Xu, Jinlong (Frontiers in Physiology, 2025)
Cold acclimation refers to the gradual process by which individuals adapt to cold environments. With the increasing impact of global climate change and the growing popularity of extreme sports, research on cold acclimation has attracted significant attention in fields such as sports medicine, psychology, and physiology. Evidence indicates that cold acclimation enhances athletic performance, promotes health, and contributes to disease prevention. However, much of the current research primarily examines the interplay between physiological mechanisms and psychological adaptations, with limited systematic evaluation of its broader effects. This review provides an in-depth analysis of the physiological adaptations associated with cold acclimation, including cardiovascular adjustments, metabolic regulation, and modification in immune responses. Additionally, the psychological effects of cold acclimation are examined, highlighting its potential to improve mental wellbeing. The review further explores practical applications of cold acclimation, such as optimizing athletic performance, promoting overall health, and mitigating disease risks. Finally, this paper identifies gaps in current knowledge and proposes future research directions to offer a theoretical framework and practical guidance for the expanded application of cold acclimation.